Perancangan dan Pembuatan Modul Data Mining Market Basket Analysis pada Odoo dengan Studi Kasus Supermarket X - Stefani Natalia Hendratha; Yulia Yulia; Gregorius Satia Budhi (Jurnal Infra, 2016)
Odoo Enterprise Resource Planning (ERP) system storing company’s transaction data. However, Odoo doesn't have a module for managing data. It takes a module for managing data into useful information.Based on the above problems, a module for data mining Market Basket Analysis is being designed. This module uses FP-Growth algorithm by utilizing the sales transaction data.For the testing, this module using data from X Supermarket. The final result of this module is an association rule from data mining process. The rule is shown in the form of narrative and graphics making them easier to understand